Evaluation the Usage of Treated Shrimp Waste as Protein Source in Broiler Diet - Septinova, D; Kurtini, T; Tantalo, S (ANIMAL PRODUCTION, 2010)
The objective of the research was to know the best method of processed-shrimp wastes on protein consumption and retention.  Experiment was designed using completely randomized design with five treatments of ration and four replications. Treatments were  basal ration  with added by 5% shrimp waste.  Treatments were D0 (basal diet  +  non treated shrimp waste), D1 (basal diet  + shrimp waste hydrolyzed by 3% NaOH), D2 (basal diet + shrimp waste hydrolyzed by 6% NaOH), D3 (basal diet + shrimp waste hydrolyzed by 5% H2O2), and D4 (basal diet  + shrimp waste fermented by Aspergillus niger). The total number of treated chicken was 20 broiler of MB 202 strain.  To compare the effect of treatments, data was analyzed using  least square difference.  Results showed that the treated shrimp waste had potential to use as protein source in broiler diet and the best consumption and retention protein was found in hydrolysis shrimp waste by 3% NaOH and 5% H2O.  (Animal Production 12(1): 1-5 (2010)Key Words:  shrimp waste, protein consumption, protein retention, broiler, Aspergillus niger